Analisis wacana kritis atas aspek sosial dari isu keberlanjutan - Raymond, Charlie; Andono, Fidelis Arastyo (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – The purpose of this study is to explain the emerging narratives about the social aspects of sustainability issues in companies that belong to the technology sector of the new economy listing board. Methods – The paradigm used in this research is discourse analysis. Researchers used the document analysis method that focus more on social aspects due to the indirect and low impact in this studied sector. Findings - This research unravel the emerging narrative amongst companies’ reports in the new economy listing board technology. Those are compliant, transparent, and strongly committed to running social programs to contribute the SDGs. These narratives are confirmed by the triangulations in the mass media that demonstrated the real conditions. In conclusion, the emerging naratives bring about the message that elaborate the focus of the company in addressing the sustainability issues, which is about compliance or achieving certain targets. Implications - This research can contribute to add insights in sustainability research and the researcher wants to show that the public can see the narrative built on sustainability reports that are reported on sustainability issues. Originality - Previous research has mostly discussed the manufacturing and banking sectors while the technology sector is still very rarely studied.